2008
DOI: 10.1063/1.3021477
|View full text |Cite
|
Sign up to set email alerts
|

Permeability calculations in three-dimensional isotropic and oriented fiber networks

Abstract: Hydraulic permeabilities of fiber networks are of interest for many applications and have been studied extensively. There is little work, however, on permeability calculations in three-dimensional random networks. Computational power is now sufficient to calculate permeabilities directly by constructing artificial fiber networks and simulating flow through them. Even with today's high-performance computers, however, such an approach would be infeasible for large simulations. It is therefore necessary to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 57 publications
1
72
0
Order By: Relevance
“…Note that another definition of the fiber orientation tensor was proposed by Stylianopoulos et al, 31 in which the fiber lengths l i and the total length of fibers l tot are also considered. The trace of X ½ is always equal to 1.…”
Section: Resultsmentioning
confidence: 99%
“…Note that another definition of the fiber orientation tensor was proposed by Stylianopoulos et al, 31 in which the fiber lengths l i and the total length of fibers l tot are also considered. The trace of X ½ is always equal to 1.…”
Section: Resultsmentioning
confidence: 99%
“…Structural features involving curvature and aspect ratio of fibers on the permeability were also determined. The virtual geometric models [6,7], however, were constructed without sufficient verification by comparing to the real structures. Recently, X-ray tomography has rapidly developed and has been widely applied to material science, especially in the non-destructive reconstruction of porous materials, such as granular materials [8], metal foams [9], and fiber materials [10].…”
Section: Related Researchmentioning
confidence: 99%
“…Stylianopoluos et al [6] used finite-element simulation to study permeability in fibrous material with isotropic and oriented fiber arrangements. Specifically, aligned networks were generated by selecting directional vectors from an anisotropic distribution and the impact of porosity on permeability was discussed.…”
Section: Related Researchmentioning
confidence: 99%
“…This leads to an assumption of a body of hair as a porous medium, which has also been adopted by the previous hair-fluid coupling models in graphics. Stylianopoulos et al [2008] performed direct simulations of fluid flowing through submerged fiber assemblies in order to derive an empirical coarse-scale drag/permeability model depending on fiber volume fraction, radius, and orientation. We adopt this drag model in our work.…”
Section: Related Workmentioning
confidence: 99%
“…Both depend on the specific submerged structure through the angle ϑ between the hair direction and the direction of relative velocity δu (x )/∥δu (x )∥. We adopt an empirical drag force model [Stylianopoulos et al 2008] which emerged from a study of the permeability of oriented fiber networks. Experiments have shown that the longitudinal drag d ∥ (along the hair direction) is different from the perpendicular drag d ⊥ (normal to the hair direction).…”
Section: Darcy-forchheimer Drag Force For Submerged Hairsmentioning
confidence: 99%